Nilai-Nilai Karakter dalam Corak Hukum Adat Tradisi Lisan Jambi sebagai Penguatan Profil Pelajar Pancasila - Yusrizal; Harti, Laspida; Baitulah; Tulus Akbar, Muhammad (PT. Meja Ilmiah Publikasi, 2026)
The oral tradition of Jambi customary proverbs embodies patterns of customary law that reflect character values relevant to the Pancasila Student Profile. This study aims to describe the patterns of customary law (communality, deliberation/consensus, traditional, visual) in Jambi customary proverbs and link them to the six dimensions of the Pancasila Student Profile. Employing a qualitative approach with descriptive methods and content analysis, this research analyzes 12 documented examples of Jambi seloko/proverbs. Data were collected through document studies and analyzed using a modified Mayring procedure. Data validity was ensured through source and theory triangulation. The findings indicate that: (1) the communality pattern is closely related to the dimensions of mutual cooperation and independence; (2) the deliberation/consensus pattern supports the dimensions of critical reasoning, mutual cooperation, and global diversity; (3) the traditional pattern bolsters the dimensions of faith, piety, noble character, and global diversity; (4) the visual pattern strengthens the dimensions of creativity and critical reasoning. These findings demonstrate that Jambi customary proverbs can be integrated into learning and Profil Pelajar Pancasila strengthening projects (P5) through the design of intracurricular, cocurricular activities, and projects that utilize proverbs as teaching materials and media for value reflection. Research implications include the development of teaching materials, culturally grounded P5 project designs, and teacher training in utilizing oral traditions for character education based on the Merdeka Curriculum.